Understanding the fouling of UF/MF hollow fibres of biologically treated wastewaters using advanced EfOM characterization and statistical tools - Filloux, E.; Labanowski, J.; Croue, Jean-Philippe (2012)
Five secondary effluents and a river water source were characterized using size exclusion chromatography (LC-OCD-UVD-OND) and emission-excitation matrix (EEM) fluorescence spectroscopy in order to identify the major effluent organic matter (EfOM) fractions responsible for membrane fouling. This study showed the feasibility of coupling fluorescence EEM and LC-OCD-UVD-OND to investigate the fouling potential as well as a means to differentiate natural organic matter (NOM) from EfOM. The secondary effluents and river water showed a significant difference in organic matter characteristics and fouling potential, highlighting the importance of biological processes and the feed water source on EfOM characteristics and fouling potential. On the basis of statistical analysis, protein-like substances were found to be highly correlated to the fouling potential of secondary effluents. © 2012 Elsevier Ltd.